Analisis Faktor Yang Mempengaruhi Nasabah Non Muslim Menjadi Nasabah Di USPPS Ausath Blokagung Karangdoro Kecamatan Tegalsari Kabupaten Banyuwangi - Suprapto, Ribut; Inayah, Nurul; Anjastika, Anggi (JPSDa: Jurnal Perbankan Syariah Darussalam, 2024)
This study aims to determine the effect of religio us stimuli, services, promotions, and profit sharing on the interest of non-Muslim customers at Uspps Ausath Blokagung. (X1), service (X2), promotion (X3), profit sharing (X4) as independent variables and interest of non-Muslim customers (Y) as variables. bound (dependent). Sampling technique with probability sampling. The data collection is done by means of interviews, observation, questionnaires (questionnaire) and documentation. The results showed that the partial test (1) religious stimuli had a positive and significant effect on the interest of non-Muslim customers at Uspps Ausath Blokagung, having a tcount value of 2.987 which is greater than ttable 0.374 with a significant probability level of 0.006 which is smaller than 0.05 which is means significant value. (2) service has no significant effect on the interest of non-Muslim customers in Uspps Ausat Blokagung. (3) promotion has no significant effect on the interest of non-Muslim customers at Uspps Ausath Blokagung. (4) profit sharing has no significant effect on the intention of non-Muslim customers at Uspps Ausath Blokagung. (5) Meanwhile, from the simultaneous testing of the F test, it is known that religious stimuli, services, promotions and profit sharing on the interest of non-Muslim.